Comparison study of two different isolation and purification method for rice tungro bacilliform virus (RTBV) - Uda, Muhammad Nur Aiman; Che Man, Hasfalina; Abd Aziz, Samsuzana; Ishak, Zamri; Bunawan, Siti Noraini; Wahid, Nur Sabrina; Hashim, Uda (Elsevier, 2014)
This paper studies two different virus purification methods for rice tungro bacilliform virus. In the first method, infected samples were extracted using liquid nitrogen with mixture of 10% Cellulases whereas the second method used alternate spinning of the infected samples at high and low speed with 5% Cellulases. Viral particles from both methods were examined by transmission electron microscopy (TEM) and rod-shaped with rounded ends was only seen on samples that were extracted with method 2. The estimated purity and concentration of method 2 is higher compare to method 1 which are 1.362 and 1.608 mg/ml and 0.958 and 0.299 mg/ml respectively.